Microneedle loaded with active ingredient nano-particles of Chinese herbaceous peony and liquorice decoction as well as preparation method and application of microneedle
By preparing microneedles loaded with targeted nanoparticles of the effective components of Shaoyao Gancao Decoction, the problem of blood-brain barrier crossing in existing PD treatment has been solved, efficient targeted delivery and precise treatment of drugs have been achieved, and the treatment effect and safety have been improved.
Patent Information
- Application Number
- CN202510623161.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-09-05
AI Technical Summary
Existing PD treatments cannot effectively cross the blood-brain barrier, resulting in limited drug efficacy and possible side effects. The active ingredients of the traditional Chinese medicine Shaoyao Gancao Decoction are difficult to cross the blood-brain barrier and target the lesions.
Nanoparticles of the effective components of Shaoyao Gancao Decoction were wrapped with silk fibroin, and Angiopep-2 peptide was modified on their surface to prepare microneedles loaded with targeted nanoparticles. The microneedles were then delivered through a transdermal drug delivery system to cross the blood-brain barrier and target the Parkinson's disease lesions.
It significantly improves the bioavailability and targeting of drugs, increases drug concentration in lesions, achieves precise drug delivery, reduces systemic toxic side effects, and has good safety and therapeutic effects.
Smart Images

Figure CN120585718A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomedicine technology, and in particular to a microneedle loaded with nanoparticles of the effective component of Shaoyao Gancao Decoction, and a preparation method and application thereof. Background Art
[0002] Parkinson's disease (PD) was first proposed in 1817. According to epidemiological data analysis, the prevalence of PD is significantly positively correlated with the patient's age. Clinically, PD is mainly manifested by movement disorders and cognitive dysfunction. Current PD treatments mainly include deep brain stimulation, exercise intervention, and drug therapy, but these methods mainly relieve symptoms and cannot cure the disease. In particular, drug therapy, due to the existence of the blood-brain barrier (BBB), many effective drugs have difficulty breaking through this barrier, resulting in a significant reduction in efficacy. The BBB restricts the penetration of most large molecules and 98% of small molecule drugs, thus severely restricting the clinical effectiveness of anti-PD drugs. At the same time, long-term drug use may cause serious side effects, increased drug resistance, and limited BBB permeability, making it difficult to achieve lasting efficacy. The task of developing efficient PD treatments is urgent.
[0003] Ferroptosis is an iron-dependent form of programmed cell death. Its mechanism of action is that, under the action of iron, intracellular reactive oxygen species catalyze the oxidation of polyunsaturated fatty acids on lipid membranes to produce toxic lipid peroxides, ultimately causing cell membrane damage. Due to the brain's unique lipid metabolism structure, high metabolic rate, and low antioxidant defenses, iron ions tend to accumulate in the brain, making it more susceptible to ferroptosis. Previous studies have suggested that ferroptosis may be associated with the pathogenesis of Parkinson's disease (PD), but its specific mechanisms require further investigation. The DHODH-CoQH2 axis inhibits ferroptosis by promoting the reduction of DHO and CoQ to OA and CoQH2, slowing the conversion of unsaturated fatty acids into harmful lipid peroxides, thereby inhibiting ferroptosis and potentially treating PD.
[0004] Traditional Chinese Medicine (TCM) theory posits that the onset of Parkinson's disease (PD) is associated with liver yin deficiency and internal liver wind. Nourishing yin, relaxing tendons, and extinguishing wind are key treatments. Peony and Licorice Decoction, derived from the Treatise on Febrile Diseases, boasts the benefits of nourishing yin, relaxing tendons, and extinguishing wind. Studies have shown that this prescription can protect damaged neurons in PD by alleviating oxidative stress and inflammatory damage, thereby treating PD. Peony has a bitter and sour flavor, while licorice has a sweet and neutral flavor. The two complement each other, nourishing the blood, moistening yin deficiency, restoring yin fluid, and nourishing tendons and veins. Summary of the Invention
[0005] In order to overcome the problems existing in the prior art, one of the purposes of the present invention is to provide a method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction.
[0006] The second purpose of the present invention is to provide nanoparticles of the effective component of Shaoyao Gancao Decoction obtained by the above preparation method.
[0007] The third object of the present invention is to provide an application of the nanoparticles of the effective components of the Shaoyao Gancao Decoction.
[0008] The fourth object of the present invention is to provide a method for preparing microneedles loaded with nanoparticles of the effective components of Shaoyao Gancao Decoction.
[0009] The fifth object of the present invention is to provide microneedles loaded with nanoparticles of the effective components of Shaoyao Gancao Decoction obtained by the above preparation method.
[0010] The sixth object of the present invention is to provide the application of the above-mentioned microneedles loaded with nanoparticles of the effective components of Shaoyao Gancao Decoction.
[0011] Paeoniflorin (PF), the core active ingredient in Paeonia lactiflora (Paeonia lactiflora), exhibits multi-target and multi-pathway pharmacological activity, such as inhibiting platelet aggregation, alleviating inflammatory pain, and protecting nerves. Glycyrrhizic acid (GA), the core active ingredient in licorice, exhibits remarkable diversity in its biological activities, including regulating inflammatory responses, providing antioxidant protection, promoting dopamine synthesis, and protecting mitochondrial function. Combining the two into nanoparticles can facilitate stable drug delivery.
[0012] Silk fibroin (SF), a natural polymer secreted by insects such as the silkworm, has attracted significant attention in the biomedical field due to its exceptional biocompatibility and degradability. Its superior biocompatibility, degradability, and tunable structure and properties make SF a significant advantage in the design of nano-drug delivery systems. Encapsulating SF in nanoparticles can maintain drug stability and prolong blood circulation time by modulating physicochemical properties. It can also achieve on-demand release in targeted cells in response to external stimuli, significantly reducing systemic toxic side effects.
[0013] An ideal PD drug delivery system should be able to cross the BBB, targeting therapeutic drugs to PD lesions, increasing drug concentration at the lesions and maximizing drug efficacy. Nanoparticles modified with targeting peptides can achieve BBB crossing and fully exert their therapeutic effects on PD. Nanoparticles decorated with Angiopep-2 peptide (A2 peptide) are prepared by modifying the nanoparticle surface to enable it to specifically bind to the LRP1 receptor on the BBB, thereby achieving BBB crossing and targeting PD lesions, thereby achieving targeted therapeutic effects.
[0014] Transdermal drug delivery systems (TDDS) utilize the skin's natural barrier as a drug channel to achieve systemic or localized therapeutic effects. Microneedle drug delivery systems utilize microneedles to penetrate the skin's stratum corneum, creating tiny channels for local or systemic drug delivery. By loading microneedles with nanoparticles, TDDS enables targeted transdermal drug delivery.
[0015] In order to achieve the above object, the technical solution adopted by the present invention is:
[0016] A method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction comprises the following steps:
[0017] S1, mixing the paeoniflorin aqueous solution and the glycyrrhizic acid aqueous solution, stirring, and ultrasonically disrupting to obtain a PF-GA nanoparticle solution;
[0018] S2, injecting the silk fibroin aqueous solution into the PF-GA nanoparticle solution obtained in step S1 at a uniform speed, and continuing the reaction under stirring to obtain a SF@PF-GA nanoparticle solution;
[0019] S3. After centrifuging the SF@PF-GA nanoparticle solution obtained in step S2, the supernatant was collected and filtered. The obtained filtrate was mixed with the Angiopep-2 peptide aqueous solution under stirring, and the reaction was continued under stirring to obtain the SF-A2@PF-GA nanoparticle solution.
[0020] Furthermore, the paeoniflorin aqueous solution is 1 to 10 mg / mL.
[0021] Furthermore, the concentration of the glycyrrhizic acid aqueous solution is 1 to 10 mg / mL.
[0022] Furthermore, the mass ratio of paeoniflorin to glycyrrhizic acid is 1:1 to 1:10, preferably 1:3 to 1:5, and more preferably 1:4.
[0023] Furthermore, the concentration of the silk fibroin aqueous solution is 1-10 mg / mL.
[0024] Furthermore, the amount of the silk fibroin aqueous solution is calculated based on a mass ratio of silk fibroin to paeoniflorin of 1:1 to 1:10, preferably 1:1 to 1:3, and more preferably 1:2.
[0025] Furthermore, the concentration of the Angiopep-2 peptide aqueous solution is 1 to 10 mg / mL.
[0026] Furthermore, the amount of the Angiopep-2 peptide aqueous solution is calculated based on a mass ratio of Angiopep-2 peptide: paeoniflorin of 1:1 to 1:10, preferably 1:1 to 1:3, and more preferably 1:2.
[0027] Furthermore, the stirring conditions in step S1 are: temperature 20° C., rotation speed 100-1500 rpm, and time 1-2 hours.
[0028] Furthermore, the conditions of the ultrasonic crushing treatment in step S1 are: power 240 W, cycle 3 s, interval 2 s, and working cycle 20 minutes.
[0029] Furthermore, the stirring conditions in step S2 are: a rotation speed of 500 to 1000 rpm and a time of 2 to 3 hours.
[0030] Furthermore, the injection flow rate in step S3 is 0.1 to 0.8 mL / min, preferably 0.8 mL / min.
[0031] Furthermore, the stirring and centrifuging conditions in step S3 are 10,000 to 15,000 rpm and the time is 10 to 15 minutes.
[0032] Furthermore, the filtration in step S3 is filtration through a 0.22 μm aqueous phase filter membrane.
[0033] Furthermore, the stirring conditions in step S3 are: temperature 25° C., rotation speed 600-1000 rpm, and time 2-3 hours.
[0034] Nanoparticles of the effective component of Shaoyao Gancao Decoction are obtained by the above preparation method.
[0035] A method for preparing a microneedle loaded with nanoparticles comprises the following steps:
[0036] T1. Weigh methacrylic anhydride-modified hyaluronic acid and dissolve it in the above SF-A2@PF-GA nanoparticle solution;
[0037] T2, spreading the mixed solution in the PDMS mold;
[0038] T3. After ensuring that the material is flush with the mold, place the mold in a centrifuge;
[0039] T4. Place the mold in an oven for drying;
[0040] T5. Use ultraviolet light to irradiate the mold;
[0041] T6. Place the mold in an oven for secondary drying.
[0042] Furthermore, the amount of the methacrylic anhydride hyaluronic acid is calculated based on a mass ratio of methacrylic anhydride hyaluronic acid to paeoniflorin of 1:1 to 1:10, preferably 1:8 to 1:10, and more preferably 1:9.
[0043] Furthermore, the centrifugal conditions are: rotation speed 2000±500rpm, time 3±1min.
[0044] Furthermore, the drying treatment conditions are: temperature 25±1°C, time 4±1 hours.
[0045] Furthermore, the irradiation conditions are: wavelength 365nm, time 5±1 minutes.
[0046] Furthermore, the conditions of the secondary drying treatment are: temperature: 37±1°C, 12±2 hours.
[0047] Furthermore, the parameters of the mold are as follows: the needle shape is a regular tetrahedron, the needle length is 800 μm, the bottom side length is 380×380 μm, the needle tip spacing is 800 μm, the array number is 15×15, the needle distribution area is 11.58×11.58 mm, the overall patch size is 15.2×15.2 mm, the groove depth is 2 μm, and the needle tip size is 18 μm.
[0048] A microneedle loaded with targeted Shaoyao Gancao Decoction effective component nanoparticles is obtained by the above preparation method.
[0049] The application of the above-mentioned microneedles loaded with targeted Shaoyao Gancao Decoction effective component nanoparticles in the preparation of drugs for treating Parkinson's disease.
[0050] Furthermore, the drug is a drug for treating Parkinson's disease by transdermal administration.
[0051] The present invention has the following advantages and effects compared to the prior art:
[0052] The present invention uses PF and GA to prepare PF-GA nanoparticles through an antisolvent precipitation method, and uses a confined liquid jet precipitation method to allow silk fibroin to complete the encapsulation of PF-GA nanoparticles to form SF@PF-GA nanoparticles. The surface of the SF@PF-GA nanoparticles is modified with the BBB-targeting peptide A2 peptide to obtain BBB-targeted PD nanoparticles - SF-A2@PF-GA nanoparticles. By fusing methacryloylated hyaluronic acid HAMA with a nanoparticle solution and adding it to a microneedle mold, microneedles loaded with SF-A2@PF-GA nanoparticles targeting the BBB are prepared. The microneedles loaded with targeted Shaoyao Gancao Decoction effective component nanoparticles specifically bind to the LRP1 receptor on the BBB through the TDDS administration route, cross the BBB and target the mitochondrial DHODH in the PD lesions, inhibit ferroptosis, and thus treat PD.
[0053] The microneedles provided by the present invention are loaded with nanoparticles of the effective components of Shaoyao Gancao Decoction with BBB targeting, and the bioavailability, specific distribution and controlled drug release performance of PF and GA are significantly improved, which has a positive effect on the long circulation of drugs in the body; they show good safety in PC12 neural cells; at the same time, the multifunctional synergistic effect of SF-A2@PF-GA nanoparticles formed by PF-GA encapsulated by SF modified with A2 peptide can significantly improve the targeting and anti-ferroptosis function of the nanoparticles; they have BBB targeting, can increase the accumulation of drugs in PD lesions, have the advantage of precise drug delivery, and have good application prospects.
[0054] The materials used in the present invention are derived from pharmaceutical excipients approved by the FDA and have excellent biocompatibility and high safety.
[0055] The invention has a simple process and a fast preparation speed and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 TEM characterization images of the nanoparticles prepared in Example 1: A is the TEM image of PF-GA nanoparticles, scale: 200 nm; B is the TEM image of SF@PF-GA nanoparticles, scale: 200 nm; C. TEM image of SF-A2@PF-GA nanoparticles, scale: 100 nm.
[0057] Figure 2 This is the particle size distribution diagram of SF-A2@PF-GA nanoparticles in Example 1.
[0058] Figure 3 This is the SEM characterization image of SF-A2@PF-GA nanoparticles in Example 1; scale bar: 200 nm.
[0059] Figure 4TEM comparison images of SF-A2@PF-GA nanoparticles in Example 1 before and after storage at -20°C for one month.
[0060] Figure 5 FTIR characterization diagram of the nanoparticles and the monomers used to prepare the nanoparticles in Example 1.
[0061] Figure 6 1 is the XRD characterization diagram of the nanoparticles and the monomers used to prepare the nanoparticles in Example 1.
[0062] Figure 7 The DSC characterization diagram of the nanoparticles in Example 1 and the monomers used to prepare the nanoparticles.
[0063] Figure 8 This is the SEM characterization image of the SF-A2@PF-GA microneedle in Example 2.
[0064] Figure 9 This is a characterization diagram of the hardness test of SF-A2@PF-GA microneedles in Example 2.
[0065] Figure 10 This is the H&E characterization image of the SF-A2@PF-GA microneedle after piercing the mouse skin in Example 2.
[0066] Figure 11 This is the mechanics-force-curve diagram of the load-bearing test of the SF-A2@PF-GA microneedles in Example 2.
[0067] Figure 12 Characterization diagram of the needle tip morphology of the SF-A2@PF-GA microneedle in Example 2 under different gravity; A. Appearance of the microneedle after applying 50g; B. Appearance of the microneedle after applying 100g; C. Appearance of the microneedle after applying 250g; D. Appearance of the microneedle after applying 500g.
[0068] Figure 13 This is a diagram showing the in vitro experimental results of the neuroprotective effect of SF-A2@PF-GA nanoparticles in Example 3.
[0069] Figure 14 This is a TEM characterization of the cell morphology of SF-A2@PF-GA nanoparticle cell intervention in Example 5.
[0070] Figure 15 This is a diagram showing the in vitro experimental results of the ferroptosis inhibition effect of SF-A2@PF-GA nanoparticles in Example 4.
[0071] Figure 16 This is the behavioral evaluation result of the in vivo experiment of SF-A2@PF-GA microneedles in Example 6: water maze behavioral trajectory diagram.
[0072] Figure 17 Figure 1 shows the behavioral evaluation results of the in vivo experiment of SF-A2@PF-GA microneedles in Example 6: water maze behavioral related data results.
[0073] Figure 18 Graph showing the behavioral evaluation results of the in vivo experiment of SF-A2@PF-GA microneedles in Example 6: Y-maze behavioral indicators.
[0074] Figure 19 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: O-maze behavioral trajectory diagram.
[0075] Figure 20 Figure 1 shows the O-maze behavioral evaluation results of the in vivo SF-A2@PF-GA microneedle experiment in Example 6: open-arm movement related data.
[0076] Figure 21 Figure 1 shows the behavioral evaluation results of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: O-maze behavioral closed-arm movement related data results.
[0077] Figure 22 This is the result of the in vivo behavioral evaluation of the SF-A2@PF-GA microneedles in Example 6: open field behavioral trajectory diagram.
[0078] Figure 23 Figure 6 shows some results of the open field behavior data of the in vivo experiment of SF-A2@PF-GA microneedles.
[0079] Figure 24 This is a partial result diagram of the open field behavior-related data of the in vivo experiment of SF-A2@PF-GA microneedles in Example 6.
[0080] Figure 25 Figure 1 shows the behavioral evaluation results of the in vivo experiment of SF-A2@PF-GA microneedles in Example 6: data related to the rotarod test.
[0081] Figure 26 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedles in vivo experiment in Example 6: data results related to the pole climbing experiment.
[0082] Figure 27 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: paw area-time curve before and after the gait analysis experiment.
[0083] Figure 28 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: the data results of the limb swing duration in the gait analysis experiment.
[0084] Figure 29 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: the data results of the limb swing amplitude in the gait analysis experiment.
[0085] Figure 30 These are the behavioral evaluation results of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: data on the duration of limb touch in the gait analysis experiment.
[0086] Figure 31 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: the data results of the stride length of the limbs in the gait analysis experiment.
[0087] Figure 32 This is the result of the behavioral evaluation of the SF-A2@PF-GA microneedle in vivo experiment in Example 6: the data results of the stride length of the limbs in the gait analysis experiment.
[0088] Figure 33 This is a TEM characterization image of the mouse midbrain tissue in the in vivo experiment of SF-A2@PF-GA microneedles in Example 6.
[0089] Figure 34 This is a diagram evaluating the iron ion level in brain tissue of mice subjected to the in vivo SF-A2@PF-GA microneedle experiment in Example 6.
[0090] Figure 35 This is a graph showing the expression levels of DHODH, TH, GPX4, and α-syn proteins in the midbrain tissue of mice in the in vivo SF-A2@PF-GA microneedle experiment in Example 6.
[0091] Figure 36 This is a quantitative result graph of the expression levels of proteins such as DHODH, TH, GPX4 and α-syn in the midbrain tissue of mice in the in vivo experiment of SF-A2@PF-GA microneedles in Example 6.
[0092] Figure 37 This is a graph showing the weight change trend of mice in the SF-A2@PF-GA microneedle in vivo experiment in Example 6.
[0093] Figure 38 This is a graph showing the specific blood routine and biochemical data results of mice in the SF-A2@PF-GA microneedle in vivo experiment in Example 6.
[0094] Figure 39 This is the H&E staining characterization of the five internal organs of mice in the SF-A2@PF-GA microneedle in vivo experiment in Example 6.
[0095] Figure 40 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0096] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0097] In this disclosure, the term "and / or" describes the relationship between associated objects, indicating that three possible relationships exist. For example, "A and / or B" can represent: A exists alone, A and B exist simultaneously, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0098] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or plural.
[0099] It should be understood that in various embodiments of the present invention, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0100] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "an", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.
[0101] The weights of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also represent the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally increased or decreased according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry, such as μg, mg, g, kg, etc.
[0102] Example 1: Preparation and characterization of targeted Shaoyao Gancao decoction active ingredient nanoparticles SF-A2@PF-GA
[0103] (1) Preparation of PF-GA nanoparticles, the active ingredient of Shaoyao Gancao Decoction:
[0104] Weigh 10 mg of PF monomer and dissolve it in 10 mL of ultrapure water to prepare a clear solution, ensuring that the PF monomer is completely dissolved; at the same time, weigh 40 mg of GA monomer and dissolve it in an equal volume of distilled water. Check whether the dissolution is complete. If necessary, slightly heat or stir to promote dissolution. After mixing the two phases of solution, place it in a magnetic stirrer at a constant temperature of 20°C and stir it continuously at 100 rpm for 1 hour to promote molecular self-assembly. The solution was treated with an ultrasonic cell disruptor. The ultrasonic conditions were set to an output power of 240 W, a working cycle of 20 minutes, and a pulse mode of 3.0 seconds of ultrasonication / 2.0 seconds of intermittent alternating operation. The purpose was to improve the dispersion of the particles and control the particle size through ultrasonic treatment.
[0105] (2) Preparation of SF@PF-GA nanoparticles of SF-encapsulated PF-GA:
[0106] Using a precision injection device, gradient SF solutions (1 mg / mL to 10 mg / mL) were quantitatively injected into the PF-GA nanoparticle solution at a flow rate of 0.8 mL / min, resulting in a mass ratio of SF to PF of 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, and 4:1, respectively. The mixture was stirred continuously at 500 rpm for 2 hours. The micromorphology of the samples was characterized by transmission electron microscopy (TEM), and the optimal blend ratio of SF solution to PF-GA nanoparticle solution was determined to be 1:2. The SF@PF-GA nanoparticles prepared under the optimal blend ratio were dispensed into sterile EP tubes and stored at -20°C for a short period of 24 hours. Storage at -20°C effectively prevented particle aggregation, maintained stability, and prevented freeze-thaw effects in the short term.
[0107] (3) Preparation of SF-A2@PF-GA nanoparticles modified with A2 peptide:
[0108] After thawing, the frozen SF@PF-GA nanoparticle solution was centrifuged at 12,000 × g for 10 minutes. The supernatant was collected and sterile-filtered using a 0.22 μm aqueous filter. The A2 peptide solution was mixed with the purified drug solution to achieve an A2 peptide to PF mass ratio of 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, and 4:1, respectively. Based on the antisolvent precipitation principle, the reaction was continued in a thermostatic magnetic stirrer (600 rpm, 25°C) for 2 hours to ensure optimal complexation between the A2 peptide and the drug-loaded micelles. The micromorphology of the complex was characterized by TEM. The optimal ratio of A2 peptide solution to SF@PF-GA nanoparticle solution was determined to be 1:2. The SF-A2@PF-GA nanoparticles prepared at the optimal ratio were dispensed into sterile EP tubes and stored at 4°C. This storage condition is suitable for short-term storage and ensures the stability of the nanoparticles.
[0109] (4) TEM and SEM characterization of PF-GA, SF@PF-GA and SF-A2@PF-GA nanoparticles:
[0110] TEM characterization showed that the particle size of PF-GA nanoparticles was about 10 nm, and they were evenly distributed and loosely arranged (e.g. Figure 1 By screening the SF concentration, the optimal concentration ratio and concentration of SF@PF-GA nanoparticles were determined. SF@PF-GA nanoparticles were successfully prepared using the condition of SF:PF = mass ratio of 1:2. The results showed that SF@PF-GA nanoparticles maintained excellent monodispersity, and the SF coating did not change the conformation or dispersion of the nanodrug (e.g. Figure 1 (shown in B).
[0111] By screening the concentration of A2 peptide, the optimal concentration ratio and concentration of SF-A2@PF-GA nanoparticles were determined. The experiment successfully prepared SF-A2@PF-GA nanoparticles (such as Figure 1 The particle size analysis results show that the particle size distribution of SF-A2@PF-GA nanoparticles is concentrated between 6nm and 9nm, with a peak value of about 7nm, showing a logarithmic normal distribution, showing good uniformity and stability (as shown in Figure 2). Figure 2 shown).
[0112] SEM characterization showed that SF-A2@PF-GA nanoparticles had a regular spherical structure, a narrow particle size distribution and a smooth surface. No significant particle aggregation occurred in the material system, confirming the good dispersion stability during its preparation process (such as Figure 3Studies have shown that a reasonable spatial arrangement between particles can significantly improve the controlled-release performance and drug loading efficiency of drug delivery systems, while the material surface exhibits a smooth and uniform distribution.
[0113] (5) Stability study of SF-A2@PF-GA nanoparticles:
[0114] According to the comparison of TEM images, there is no significant change in the morphology and particle size distribution of the nanoparticles between the fresh sample and the nanoparticles after one month of low temperature storage (-20 ° C), indicating that their physical and chemical properties remain stable (such as Figure 4 After one month of storage, the morphology of the sample is still uniformly distributed, and no obvious agglomeration is observed (as shown in Figure 1). Figure 4 (B in the figure). Particle size distribution analysis showed that the nanoparticles maintained a consistent distribution range, further supporting the excellent dispersion and dimensional stability of this nanosystem. These results demonstrate the long-term stability of this nanosystem under low-temperature storage conditions, providing a reliable basis for its application in drug delivery systems.
[0115] (6) FTIR analysis of SF-A2@PF-GA nanoparticles:
[0116] FTIR was used to systematically characterize the composition and structure of SF-A2@PF-GA nanoparticles, and the vibration modes of key functional groups and the mechanism of intermolecular interactions were analyzed.
[0117] In the FTIR spectrum of GA, important absorption peaks include 3405 cm -1 (OH bond), 2941cm -1 (CH bond), 1720cm -1 (C=O carbonyl), 1654 cm -1 (C=C double bond), etc. These characteristic peaks prove the molecular structure characteristics of GA. For PF, the FTIR spectrum shows a peak at 342 cm -1 (OH), 2929cm -1 (CH bond), 1713cm -1 (C=O ester group) and other positions, which reflect the chemical structure of PF.
[0118] The FTIR spectrum of peptide A2 showed that the -1 (OH and NH bonds), 1666cm -1 (Amide I with C=O), 1523 cm -1 (amide II with NH) and other characteristic absorption peaks, which interact with the spectral results of SF and PF-GA, indicating that A2 peptide forms a stable complex in SF-A2@PF-GA nanoparticles.
[0119] In the FTIR spectrum of SF, important absorption peaks include 3448 cm -1 (OH and NH bonds), 1654 cm -1 (Amide I with C=O bond), 1562 cm -1 (Amide II with NH bond), etc. These peaks, together with the absorption peaks of PF-GA and A2 peptide, indicate the involvement of SF. For SF-A2@PF-GA nanoparticles, their FTIR results show that the interaction between SF, A2 peptide, and PF forms a stable complex through hydrogen bonding and hydrophobic interactions, and the structure of the complex maintains stability in terms of physical and chemical properties.
[0120] Overall, FTIR analysis showed that when SF was combined with PF-GA to form SF@PF-GA nanoparticles, the absorption peak positions of amide I, II, and III bands did not change significantly, indicating that SF successfully encapsulated PF-GA and formed stable particles with a particle size of approximately 7-10 nm (e.g. Figure 5 Meanwhile, FTIR analysis of SF-A2@PF-GA further verified the interaction of A2 peptide with SF and PF-GA, which provided strong evidence for the formation of stable nanoparticles.
[0121] (7) XRD analysis of SF-A2@PF-GA nanoparticles:
[0122] XRD pattern analysis Figure 6 As shown, the diffraction characteristics of the various components of the SF-A2@PF-GA nanoparticles differ significantly. The XRD patterns of GA and PF exhibit distinct and sharp diffraction peaks, indicating high crystallinity. However, the SF and A2 peptides exhibit broad diffraction peaks, suggesting they may be amorphous or poorly crystalline. Based on the XRD spectra, the diffraction peaks of SF and A2 are broad and lack distinct sharp features, further supporting the possibility of their amorphous or poorly crystalline state.
[0123] Further analysis revealed that the SF-A2@PF-GA nanoparticles exhibited transitional peaks and retained a certain degree of amorphous structure, which may contribute to improved biocompatibility and drug release properties. Combined with XRD results, it can be inferred that SF and A2 interact with the surface of PF-GA nanoparticles through physical adsorption or non-covalent interactions, forming a core-shell complex. This structure may help improve the solubility of the nanoparticles and enhance the precise targeted delivery of drugs, thereby improving the efficiency and stability of the drug delivery system.
[0124] (8) DSC analysis of SF-A2@PF-GA nanoparticles:
[0125] DSC analysis provides important information about the self-assembly process of SF-A2@PF-GA nanoparticles. Figure 7 As shown, the DSC curves of PF, GA, SF, and A2 peptides all exhibit typical thermal behavior. The melting process of PF and GA exhibits distinct endothermic peaks, reflecting their high crystallinity. The sharp melting peaks indicate that these substances possessed good crystallinity during preparation. In contrast, the endothermic peaks of SF and A2 peptides are broad, suggesting that they may be in an amorphous or low-crystalline state. Changes in the endothermic peaks are associated with changes in molecular conformation and the melting of aggregates.
[0126] In the DSC curve of SF-A2@PF-GA nanoparticles, the low-temperature endothermic peak is primarily associated with water volatilization, silk fibroin chain scission, and A2 peptide depolymerization. Analysis of the endothermic peak positions suggests that water volatilization occurs around 50°C, while silk fibroin chain scission and A2 peptide depolymerization occur at lower temperatures, indicating that the nanoparticles undergo initial structural changes at low temperatures. The high-temperature endothermic peak primarily reflects the melting process of the nanoparticles and the cross-linking and polymerization between their components. It typically occurs at higher temperatures, indicating the thermal stability of the nanoparticles and the interactions between their components.
[0127] Comprehensive analysis revealed that SF and A2 formed a core-shell structure on the surface of the PF-GA particles through physical adsorption or non-covalent interactions. The stability of this structure is closely related to hydrogen bonding and hydrophobic interactions. Further analysis of DSC data, combined with FTIR and other characterization techniques, confirmed the importance of these interactions in nanoparticle stability, confirming their potential for drug delivery applications.
[0128] Example 2: Preparation and characterization of SF-A2@PF-GA loaded microneedles
[0129] (1) Preparation of SF-A2@PF-GA loaded microneedles
[0130] After mixing HAMA solid and SF-A2@PF-GA nanoparticle solution at a mass ratio of HAMA:PF = 1:9, the mixture was then deposited into a PDMS mold. The mold parameters were as follows: the needles were regular square pyramids with a length of 800 μm, a base side of 380 × 380 μm, a tip spacing of 800 μm, an array of 15 × 15 needles, a distribution area of 11.58 × 11.58 mm, an overall patch size of 15.2 × 15.2 mm, a groove depth of 2 μm, and a tip size of 18 μm. After ensuring that the material was flush with the mold surface, the mold was placed in a centrifuge at 2000 rpm for 3 minutes to remove bubbles and promote uniform distribution. After centrifugation, the mold was placed in a 25°C oven for 4 hours for heat treatment, with the solution replenished every 2 hours to ensure uniformity and stability. Subsequently, the sample was irradiated with a 365 nm UV lamp for 5 minutes to cure the material and form the mold. The UV irradiation wavelength was chosen to be 365 nm because it effectively activates the crosslinker in HAMA, thereby accelerating the curing process of the material. Finally, to set the shape and remove excess solvent, the mold was placed in a dry environment at 37°C for a secondary treatment. This treatment aims to improve the mechanical strength of the microneedles and ensure the stability of the material during storage.
[0131] (2) SEM imaging results of SF-A2@PF-GA microneedles
[0132] As shown in the SEM image, the microneedles are in the shape of regular quadrangular pyramids, with regular arrangement and uniform spacing. The needle tips are sharp, the surface is smooth, and there is no obvious aggregation, showing good uniformity and structural stability (such as Figure 8 This sophisticated structural design not only allows for efficient penetration of the skin or other biological tissues with minimal external force, ensuring uniform drug release, but also reduces tissue damage during puncture, improving patient comfort.
[0133] (3) Hardness test of SF-A2@PF-GA microneedles
[0134] Compressive strength and elastic modulus help the microneedle maintain structural stability when external force is applied, avoiding breakage or deformation during the puncture process. In order to systematically investigate the mechanical properties and drug delivery performance of SF-A2@PF-GA microneedles, this experiment used a texture analyzer to evaluate them. The test results are as follows Figure 9 As shown, the microneedles possess excellent mechanical properties: a compressive strength of 297.6N, an elastic modulus of 0.26N / mm², and a hardness test result of 119.686N·mm. These parameters demonstrate that the microneedles of the present invention exhibit excellent mechanical strength and elasticity, maintaining a stable morphology and structure while penetrating epidermal tissue, thereby effectively exerting their penetrating effect.
[0135] (4) Observation of mouse skin sections after SF-A2@PF-GA microneedle insertion
[0136] After microneedle treatment of mice, skin sections were taken and H&E staining was performed. The results showed that the microneedles could effectively penetrate the surface layer of the skin and penetrate deep into the dermis. Figure 10 As shown in Figure 2, the microneedles have broken through the epidermis and penetrated deep into the dermis, entering deeper skin tissue. This observation suggests that microneedles can not only penetrate the epidermis but also reach the dermis, thereby helping to promote drug penetration and activate the skin's self-repair mechanism.
[0137] (5) SF-A2@PF-GA microneedle load-bearing capacity test results
[0138] The force-displacement curve reflects the mechanical properties of the microneedle. Figure 11 、 Figure 12 As shown, under a 50g load, the initial force increases slowly, indicating low microneedle rigidity, making it suitable for light load environments. Under a 100g load, the force increases rapidly, indicating moderate rigidity. Under a 250g load, the force increases significantly, indicating high rigidity. Under a 500g load, the force increases rapidly, and the force variation increases with increasing microneedle length, indicating high rigidity. These analysis results demonstrate that microneedle rigidity increases with load, enabling it to provide sufficient penetration force under higher loads, meeting the requirements of TDDS drug delivery systems for penetrating skin or biological tissues.
[0139] Comparative Example 1
[0140] Nanoparticles were prepared by referring to Example 1, except that in step (2), the SF solution and the PF-GA solution were mixed in SF:PF mass ratios of 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, and 4:1, and the composite was prepared using an antisolvent precipitation method. The results showed that when the SF:PF mass ratio was 1:2, the nanoparticles exhibited optimal morphology and size in TEM images, with a narrower particle size distribution and better dispersibility.
[0141] Comparative Example 2
[0142] Nanoparticles were prepared by referring to Example 1, except that in step (3), the A2 peptide solution and the SF@PF-GA nanoparticle solution were mixed in mass ratios of A2 peptide:PF = 1:1, 1:2, 1:3, 1:4, 2:1, 3:1, and 4:1, and the composite was prepared using an antisolvent precipitation method. The results showed that when the A2 peptide:PF mass ratio was 1:2, the nanoparticles exhibited the best morphology and size in TEM images, with a narrower particle size distribution and better dispersibility.
[0143] Comparative Example 3
[0144] Microneedles were prepared according to Example 2, except that HAMA and the SF-A2@PF-GA nanoparticle solution were mixed and stirred at HAMA:PF mass ratios of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, and 1:10. Results showed that a HAMA:PF mass ratio of 1:9 optimally met the concentration requirements for microneedle preparation.
[0145] Example 3: Neuroprotective Effect of SF-A2@PF-GA Nanoparticles
[0146] The present invention adopts MPP + The neuroprotective effect of SF-A2@PF-GA nanoparticles was tested in the induced PD cell model. PC12 cell suspension (seeding density 1×10 4 Cells / well) were seeded in 96-well plates and cultured at 37°C for 24 hours to form a stable cell monolayer. Different gradient concentrations of SF-A2@PF-GA nanoparticles (1, 3, 6, 12, 25, 50, 100 μg / mL) were used for pretreatment for 24 hours, and then 4 mM MPP was added to the cells. + , and co-treated in a cell culture incubator at 37°C, 5% CO2 for 24 hours. After the intervention, the drug-containing medium was gently removed using a sterile pipette, and 100 μL of basal medium containing 10% CCK-8 detection reagent (v / v) was added to each well. The cells were incubated at 37°C in the dark for 1.5 hours, and cell metabolic activity was quantitatively analyzed using a full-wavelength microplate reader (main wavelength 450 nm, reference wavelength 630 nm). The relative cell viability was calculated using the following formula:
[0147]
[0148] The results are as follows Figure 13 As shown, after all groups were exposed to 4 mM MPP+ for 24 hours, the survival rate of cells treated with MPP+ alone was approximately 60%. However, in the group treated with 12 μg / mL of SF-A2@PF-GA nanoparticles, cell survival rate increased significantly, indicating that this concentration has the optimal neuroprotective effect. A one-way analysis of variance showed that the experimental results were statistically significant (P < 0.0001), indicating that 12 μg / mL of SF-A2@PF-GA nanoparticles has the optimal neuroprotective effect.
[0149] Example 4: Ferroptosis Inhibition Effect of SF-A2@PF-GA Nanoparticles
[0150] The present invention adopts MPP + The neuroprotective effects of PF-GA and SF-A2@PF-GA were compared in the PD cell model induced by PF-GA. PC12 cell suspension (seeding density 1×104 Cells / well) were seeded in 96-well plates and cultured at 37°C for 24 hours to form a stable cell monolayer. The optimal intervention concentration of SF-A2@PF-GA obtained in the previous experiment was used to perform intervention experiments on cells according to the cell experiment grouping of this example. Each group was pretreated with the drug intervention concentration for 24 hours and then treated with 4mM MPP. + , pretreated in a cell culture incubator (37°C, 5% CO2) for 24 hours, and then treated with 4 mM MPP + The cells were co-treated for 24 hours in a cell culture incubator at 37°C and 5% CO2 (using the ferroptosis inhibitor Fer-1 and the DHODH inhibitor BQR as controls). After the intervention, the drug-containing medium was gently removed using a sterile pipette. 100 μL of basal medium containing 10% CCK-8 detection reagent (v / v) was added to each well. The cells were incubated at 37°C in the dark for 1.5 hours, and cell metabolic activity was quantitatively analyzed using a full-wavelength microplate reader (main wavelength 450 nm, reference wavelength 630 nm). Relative cell viability was calculated using the following formula:
[0151]
[0152] The results are as follows Figure 15 All groups were exposed to 4 mM MPP as shown. + After 24 hours, only MPP + The survival rate of treated cells was approximately 60%. The survival rate of cells in the Fer-1 treatment group was significantly restored, suggesting that Fer-1 alleviated the cell damage caused by ferroptosis. In contrast, the survival rate of cells in the BQR treatment group decreased significantly, possibly because DHODH inhibition exacerbated ferroptosis and accelerated cell death. The survival rate of cells in the SF-A2@PF-GA nanoparticle treatment group was significantly increased, while the cell survival rate in the SF-A2@PF-GA nanoparticle combined with BQR treatment group was significantly higher than that in the BQR treatment group, indicating that it not only effectively inhibited ferroptosis, but also restored the cell antioxidant capacity, and reduced the incidence of ferroptosis by regulating DHODH activity, thereby significantly reducing cell damage. The results of the one-way analysis of variance showed that the experimental results were statistically significant (P<0.0001).
[0153] Example 5: TEM analysis of cell morphology after SF-A2@PF-GA nanoparticle cell intervention
[0154] Combined with TEM images, the ultrastructural changes of mitochondria, endoplasmic reticulum and cell structure in the PC12 cell PD model were systematically analyzed to evaluate the effect of SF-A2@PF-GA nanoparticles in the treatment of PD.
[0155] In terms of mitochondrial morphology: electron microscopy observations Figure 14As shown in A, the mitochondrial structure of PC12 cells in the CON group was regular and the cristae were clearly arranged, indicating that their energy metabolism function was normal; while + The treated group showed significant mitochondrial pathology, including blurred cristae, swelling, and membrane rupture, suggesting impaired mitochondrial function, which may affect cellular energy supply. The SF-A2@PF-GA group showed significant improvement in mitochondrial structure, with cristae morphology approaching normal, indicating that the drug helps restore mitochondrial function and thus improve cellular energy metabolism.
[0156] In terms of endoplasmic reticulum structure: electron microscopy observations Figure 14 As shown in B, the endoplasmic reticulum structure of PC12 cells in the CON group was intact and regular; while that in the MPP group was + The treated group showed severe ER vacuolation, suggesting cellular dysfunction, while the SF-A2@PF-GA group showed some alleviation of ER damage, with a clearer structure, indicating that the drug helps alleviate ER stress.
[0157] In cell structure observation: electron microscopy observation Figure 14 As shown in C, the PC12 cells in the CON group had intact structures and membranes; while the MPP + Cells in the treated group showed typical apoptotic features such as cytoplasmic vacuolation and cell membrane rupture. Cell morphology in the SF-A2@PF-GA group was significantly restored, with reduced cytoplasmic vacuolation, suggesting that SF-A2@PF-GA nanoparticles have a significant effect in slowing cell apoptosis and maintaining cell structure.
[0158] In summary, SF-A2@PF-GA nanoparticles significantly improved the neural damage of the PC12 cell PD model by improving mitochondrial morphology, alleviating endoplasmic reticulum damage and maintaining the integrity of cell structure, showing good neuroprotective effect.
[0159] Example 6: Pharmacodynamic evaluation of SF-A2@PF-GA microneedles targeting mitochondrial DHODH to inhibit ferroptosis in the treatment of PD in vivo
[0160] The present invention set up 5 experimental groups, each with a sample size of 16 mice. The grouping and treatment schemes are as follows:
[0161] (1) CON group: No model induction was performed, and 0.9% sodium chloride solution was injected into the tail vein every day for 5 days;
[0162] (2) MOD group: PD animal model was established by MPTP induction method, and MPTP was intraperitoneally injected at a dose of 30 mg / kg for 5 days;
[0163] (3) LD group: After the MPTP model was established, levodopa was intraperitoneally injected every other day at a dose of 30 mg / kg starting from the second day for a total of 5 days;
[0164] (4) PF-GA group: After the MPTP model was established, a mixed drug of PF-GA in a ratio of 1:4 was injected via the tail vein at a dose of 6 mg / kg every other day starting from the second day, for a total of 5 days;
[0165] (5) SF-A2@PF-GA microneedle group: After the MPTP model was established, SF-A2@PF-GA microneedle patches were applied to the Baihui (GV20), Fengfu (GV16), Taichong (LR3) and Dazhui (GV14) acupoints from the second day onwards. The treatment course was 5 days in total. The drug dose of SF-A2@PF-GA nanoparticles contained in each patch was 1.25 mg / kg.
[0166] After modeling, the mice showed motor and non-motor disorders similar to PD. After intervention on PD mice according to the above experimental groups, behavioral evaluation of each group of mice revealed that Figures 16 to 32 As shown in the data, the results of cognitive behavioral experiments (water maze test, Y maze test, elevated zero maze test) and motor function behavioral experiments (open field test, rotarod test, climbing pole test, gait test) of mice in the SF-A2@PF-GA microneedle treatment group all showed significant therapeutic effects.
[0167] like Figure 33 As shown, using transmission microscopy to observe the midbrain tissues of mice in the CON group, MOD group and SF-A2@PF-GA microneedle treatment group, it was found that the mitochondrial fiber fragmentation, myelin sheath structural disorder and synaptic vesicle depletion in the synaptic cleft of mice in the SF-A2@PF-GA microneedle treatment group were significantly improved, indicating that SF-A2@PF-GA microneedle treatment can improve the pathological damage caused by MPTP. Figures 34 to 36 As shown, the imbalance of ferroptosis-related indicators (iron ion content, DHODH, TH, GPX4 and α-syn protein expression levels) in mouse striatal tissue was significantly improved.
[0168] Biosafety evaluation included the trend of mouse body weight ( Figure 37 ), routine blood analysis, blood biochemistry analysis ( Figure 38 ), HE staining of major organs ( Figure 39 )The results showed that SF-A2@PF-GA microneedles had good biocompatibility.
[0169] Finally, it should be noted that the above embodiments are intended to illustrate the technical solutions of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction, characterized by: The steps include: S1, mixing the paeoniflorin aqueous solution and the glycyrrhizic acid aqueous solution, stirring, and ultrasonically disrupting to obtain a PF-GA nanoparticle solution; S2, injecting the silk fibroin aqueous solution into the PF-GA nanoparticle solution obtained in step S1 at a uniform speed, and continuing the reaction under stirring to obtain a SF@PF-GA nanoparticle solution; S3. After centrifuging the SF@PF-GA nanoparticle solution obtained in step S2, the supernatant was collected and filtered. The obtained filtrate was mixed with the Angiopep-2 peptide aqueous solution under stirring, and the reaction was continued under stirring to obtain the SF-A2@PF-GA nanoparticle solution.
2. The method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction according to claim 1, characterized in that: The paeoniflorin aqueous solution is 1-10 mg / mL; The concentration of the glycyrrhizic acid aqueous solution is 1 to 10 mg / mL; The concentration of the silk fibroin aqueous solution is 1 to 10 mg / mL; The concentration of the Angiopep-2 peptide aqueous solution is 1 to 10 mg / mL; The mass ratio of paeoniflorin to glycyrrhizic acid is 1:1 to 1:10; The amount of the silk fibroin aqueous solution is calculated based on a mass ratio of silk fibroin to paeoniflorin of 1:1 to 1:
10. The dosage of the Angiopep-2 peptide aqueous solution is calculated based on a mass ratio of Angiopep-2 peptide to paeoniflorin of 1:1 to 1:
10.
3. The method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction according to claim 2, characterized in that: The mass ratio of paeoniflorin to glycyrrhizic acid is 1:3 to 1:5; The amount of the silk fibroin aqueous solution is calculated based on a mass ratio of silk fibroin to paeoniflorin of 1:1 to 1:
3. The dosage of the Angiopep-2 peptide aqueous solution is calculated based on a mass ratio of Angiopep-2 peptide to paeoniflorin of 1:1 to 1:
3.
4. The method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction according to claim 3, characterized in that: The mass ratio of paeoniflorin to glycyrrhizic acid is 1:4; The amount of the silk fibroin aqueous solution is calculated based on a mass ratio of silk fibroin to paeoniflorin of 1:
2. The dosage of the Angiopep-2 peptide aqueous solution is calculated based on the mass ratio of Angiopep-2 peptide to paeoniflorin of 1:
2.
5. The method for preparing nanoparticles of the effective component of Shaoyao Gancao Decoction according to any one of claims 1 to 4, characterized in that: The stirring conditions in step S1 are: temperature 20° C., rotation speed 100-1500 rpm, and time 1-2 hours; The conditions of the ultrasonication treatment in step S1 are: power 240 W, cycle 3 s, interval 2 s, and working cycle 20 minutes; The stirring conditions in step S2 are: a rotation speed of 500 to 1000 rpm and a time of 2 to 3 hours; The injection flow rate in step S3 is 0.1 to 0.8 mL / min; The stirring and centrifuging conditions in step S3 are 10,000 to 15,000 rpm and the time is 10 to 15 minutes; The filtration described in step S3 is filtration through a 0.22 μm aqueous phase filter membrane; The stirring conditions in step S3 are: temperature 25° C., rotation speed 600-1000 rpm, and time 2-3 hours.
6. A nanoparticle of the effective component of Shaoyao Gancao Decoction, characterized by: The method is obtained by the preparation method described in any one of claims 1 to 5.
7. A method for preparing a nanoparticle-loaded microneedle, characterized by: The steps include: T1. Weigh methacrylic anhydride-modified hyaluronic acid and dissolve it in the SF-A2@PF-GA nanoparticle solution obtained by the preparation method described in any one of claims 1 to 5; T2, spreading the mixed solution in the PDMS mold; T3. After ensuring that the material is flush with the mold, place the mold in a centrifuge; T4. Place the mold in an oven for drying; T5. Use ultraviolet light to irradiate the mold; T6. Place the mold in an oven for secondary drying.
8. The method for preparing nanoparticle-loaded microneedles according to claim 7, characterized in that: The amount of the methacrylic anhydride hyaluronic acid is calculated based on a mass ratio of methacrylic anhydride hyaluronic acid to paeoniflorin of 1:8 to 1:
10. The centrifugal conditions are: speed 2000±500rpm, time 3±1min; The drying conditions are as follows: temperature 25±1°C, time 4±1 hours; The irradiation conditions are: wavelength 365nm, time 5±1 minutes; The conditions of the secondary drying treatment are: temperature: 37±1°C, 12±2 hours; The parameters of the mold are as follows: the needle shape is a regular tetrahedron, the needle length is 800 μm, the bottom side length is 380×380 μm, the needle tip spacing is 800 μm, the array number is 15×15, the needle distribution area is 11.58×11.58 mm, the overall patch size is 15.2×15.2 mm, the groove depth is 2 μm, and the needle tip size is 18 μm.
9. A microneedle loaded with targeted nanoparticles of the active ingredient of Shaoyao Gancao Decoction, characterized by: The method is obtained by the preparation method described in any one of claims 7 to 8.
10. Use of the microneedles loaded with targeted nanoparticles of the effective component of Shaoyao Gancao Decoction as claimed in claim 9 in the preparation of drugs for treating Parkinson's disease.